Cactus Pear (Opuntia Ficus-Indica) in Areas with Limited Rainfall for the Production of Biogas and Biofertilizer - Quiroz-Espinoza, M (Elsevier Ltd, 2021)
An insecure energy supply has promoted the search of alternative energies. Anaerobic digestion can produce methane from energy crops. Opuntia ficus-indica or cactus pear can produce high amounts of dry matter (DM), 10 Mg ha−1 y−1 with an average rainfall of 400 mm y−1. It is a crop with a high efficiency in the use of water (4.6 mg DM g−1 H2O) and can grow on land not currently used for the production of other crops. This review found that Opuntia productivity strongly depends on agronomic management (50 Mg ha−1 y−1). The increase in DM is reflected in an increase in the theoretical yield of biogas and methane. Opuntia cladodes have a high potential for producing methane (327 m3 CH4 Mg−1 VS) because their carbohydrates have a low fiber content and are easily degraded. To optimize the production and quality of the biogas produced from Opuntia, its cladodes would have to be mixed with other raw materials (e.g. manure, plant residues, microalgae) and C/N ratio (16–30) for microorganisms in the digestate; the pH would also have to be modified to a neutral-alkaline range (the cladodes have a pH between 3.5 and 5.5) for the same reason. The resulting digestate could be applied to the soil as a biofertilizer, improving its properties as well as crop productivity. This is important, above all, in soils in semi-arid zones. Finally, there are several challenges to validate Opuntia as an energy crop, especially from a holistic viewpoint that considers economic, social and environmental aspects. © 2021